The culture of Carthamus tinctorius L.: Main uses and genetic variability - Oliveira, Altacis Junior de (2021)
The Carthamus tinctorius L. is one of the oldest species in the world, it is an oleaginous belonging to the Asteraceae family, whose raw material is destined for several purposes. The culture has attracted the attention of researchers and industries for having high quality and quantity of oil, in this context which makes it important to conduct studies, especially in genetic improvement, which helps in the selection of superior genotypes. Therefore, the present work aimed to develop a literature review on safflower culture, showing some information on its cultivation, main uses and genetic variability. Through the study done in scientific articles, books and journals it is possible to familiarize the readers about safflower culture, because still in Brazil it is little studied and information mainly about its cultivation and production are still scarce, but some presented works show the potential that Brazil has for safflower cultivation, being necessary genetic improvement studies to extract the maximum potential of the species.Incluir o resumo em inglês.